2018
DOI: 10.1148/radiol.2017171028
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of MR Imaging in Differentiating T Staging of Bladder Cancer: A Meta-Analysis

Abstract: Purpose To assess the diagnostic accuracy of magnetic resonance (MR) imaging for differentiating stage T1 or lower tumors from stage T2 or higher tumors and to analyze the influence of different imaging protocols in patients with bladder cancer. Materials and Methods A systematic literature search for original diagnostic studies was performed in PubMed, Medline, the Cochrane Library, and Web of Science. The methodologic quality of each study was evaluated by two independent reviewers who used the Quality Asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
88
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(96 citation statements)
references
References 31 publications
(31 reference statements)
3
88
0
5
Order By: Relevance
“…The utility of the stalk in describing T stage was more recently confirmed by Wang et al [18]; our results are in accordance with those authors, as we found that 81% of NMIBC presented with a stalk. Given the growing interest in evaluating mpMRI performance in BCa local staging, three meta-analyses have recently addressed the issue, finding a pooled sensitivity of 0.87 (95% CI 0.82-0.91), 0.92 (95% CI 0.88-0.95), and 0.90 (95% CI 0.83-0.94) and specificity of 0.79 (95% CI 0.72-0.85), 0.87 (95% CI 0.78-0.93), and 0.88 (95% CI 0.77-0.94), respectively [10,11,19].…”
Section: Discussionmentioning
confidence: 99%
“…The utility of the stalk in describing T stage was more recently confirmed by Wang et al [18]; our results are in accordance with those authors, as we found that 81% of NMIBC presented with a stalk. Given the growing interest in evaluating mpMRI performance in BCa local staging, three meta-analyses have recently addressed the issue, finding a pooled sensitivity of 0.87 (95% CI 0.82-0.91), 0.92 (95% CI 0.88-0.95), and 0.90 (95% CI 0.83-0.94) and specificity of 0.79 (95% CI 0.72-0.85), 0.87 (95% CI 0.78-0.93), and 0.88 (95% CI 0.77-0.94), respectively [10,11,19].…”
Section: Discussionmentioning
confidence: 99%
“…Woo et al performed a recent meta‐analysis, with a pooled sensitivity and specificity of 0.92 and 0.87, respectively, for differentiating <T1 vs. >T2 disease . Huang et al also published a recent meta‐analysis obtaining a pooled sensitivity and specificity of 0.90 and 0.88, respectively, for differentiating <T1 vs. >T2 disease …”
Section: Mri Staging and Accuracymentioning
confidence: 99%
“…20 Huang et al also published a recent meta-analysis obtaining a pooled sensitivity and specificity of 0.90 and 0.88, respectively, for differentiating <T1 vs. >T2 disease. 21 Bladder cancer N stage criteria were modified in the more recent 7 th and 8 th editions of the AJCC Staging Manual. 62,71 N stage is now determined by the number of pathologic lymph nodes, and includes common iliac nodes as regional nodal disease.…”
Section: Mri Staging and Accuracymentioning
confidence: 99%
See 2 more Smart Citations